2012
DOI: 10.1021/ol302541j
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of the Fully Elaborated Pyrrolidinone Core of Oxazolomycin A

Abstract: The asymmetric synthesis of the key pyrrolidinone core, including a highly elaborated exocyclic carbon chain, of the γ-lactam β-lactone antibiotic oxazolomycin A is described. Principal features include the Birch reduction of an aromatic pyrrole nucleus, a late stage RuO(4) catalyzed pyrrolidine oxidation, and a highly diastereoselective organocerium addition to an aldehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 32 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…As part of our ongoing efforts to prepare oxazolomycin B, , we required an efficient synthesis of (−)-(3 R )-inthomycin C and sought to differentiate our approach by avoiding the use of the stoichiometric organotin reagents on which all previous syntheses rely. Initial investigations on the biological activity of synthetic (−)-(3 R )-inthomycin C and structural analogues on human cancer cell lines are also described for the first time.…”
mentioning
confidence: 99%
“…As part of our ongoing efforts to prepare oxazolomycin B, , we required an efficient synthesis of (−)-(3 R )-inthomycin C and sought to differentiate our approach by avoiding the use of the stoichiometric organotin reagents on which all previous syntheses rely. Initial investigations on the biological activity of synthetic (−)-(3 R )-inthomycin C and structural analogues on human cancer cell lines are also described for the first time.…”
mentioning
confidence: 99%
“…1) 1 and have established that Dieckmann 2 and aldol 3 ring closures may be used to access such systems. While a number of other groups have developed methodology to provide the relevant lactam-lactone spirocyclic and inthomycin subsets of the natural product, [4][5][6][7][8][9][10][11] we have established that some smaller structural mimics exhibit antibacterial activity [12][13][14] and therefore sought routes providing rapid access to other skeletal subsets of oxazolomycin which might similarly provide antibacterially active libraries. We recently reported that a biomimetic intramolecular aldol reaction using malonamide 2 (R 1 ¼ H, R 2 ¼ H, X ¼ OMe) derived from oxazolidine template 1 may be used to generate densely functionalised pyroglutamates of type 3, possessing two contiguous quaternary chiral centres.…”
mentioning
confidence: 99%
“…63 The synthesis commenced with Rivas and Ling N-protection of the the commercially available pyrrole 228, followed by partial Birch reduction and quenching with iodomethyl pivalate. Ester reduction afforded compound 229, which was treated with a lipase enzyme to desymmetrate the compound.…”
Section: D) Birch Reductionmentioning
confidence: 99%
“…Deprotection of the methoxymethyl (MOM) group, followed by oxidation to the corresponding carboxylic acid, provided compound 234 (Scheme 48). 63 Protection of the acid 234 with a silyl group, removal of the acetate group, and oxidation led to the desired aldehyde. The resultant aldehyde was subjected to the Nozaki-Hiyama-Kishi reaction, which is a nickel/chromium-mediated coupling reaction between an aldehyde and a vinyl halide.…”
Section: D) Birch Reductionmentioning
confidence: 99%